English Borrowings in Indonesian newspapers - Iwan Fauzi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2015)
This study represents a corpus-based study of English loan words in Bahasa Indonesia used by three foremost newspapers in Indonesia (Kompas, Koran Tempo, and Media Indonesia). There are 19,494 loan tokens of 3,538 loan types extracted from 3,671 texts published online on those media during around three months ranging from 1 April to 24 June 2012. This study compares two basic typologies of borrowing—established and non-established loans. Attestations are looked into in this study proving the evidence that the borrow ability of nouns is higher than otherword categories, linguistic typology of borrowing motivates linguistic adaptation, and word categories give a significant contribution to motivate linguistic adaptation as well.